2016
DOI: 10.1007/s10570-016-1123-7
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of methanol and the tensile strength of insulation paper: kinetics of the changes of mechanical properties during ageing

Abstract: This paper reports the temperature-dependence of methanol generation and the tensile index under ageing conditions for two paper/oil systems: one consisting of a standard wood Kraft paper and the other of a thermally-upgraded Kraft paper (TUK). A linear correlation between methanol and the tensile index for these paper/oil systems was observed in a previous study at 170°C. In the current study, the correlation was extended to a large range of temperatures (150-190°C). The experimental data were fitted with a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 18 publications
2
27
0
Order By: Relevance
“…As shown in Figure 3, a relationship exists between methanol formation and the breaking of 1,4-β-glycosidic bonds in cellulose [1]. Therefore, studies have been performed to confirm the kinetic correspondence between these two processes [27][28][29][30].…”
Section: Kinetics Of Cellulose Depolymerization and Methanol Formationmentioning
confidence: 95%
See 3 more Smart Citations
“…As shown in Figure 3, a relationship exists between methanol formation and the breaking of 1,4-β-glycosidic bonds in cellulose [1]. Therefore, studies have been performed to confirm the kinetic correspondence between these two processes [27][28][29][30].…”
Section: Kinetics Of Cellulose Depolymerization and Methanol Formationmentioning
confidence: 95%
“…Nevertheless, it is practically impossible to measure both parameters for power transformers in service. Studies of thermally accelerated ageing of paper impregnated with mineral oil revealed a quasilinear, temperature-independent correlation between the mechanical strength of paper (using the zero and wide span modes) and the cellulose's degree of polymerization [30,41,45,46,52,57,61,62,71], as seen in Figure 5. In the first part of the master curve, up to around DPv = 700, for different temperatures and types of paper, the mechanical strength of paper does not decrease with the decline in degree of polymerization [41].…”
Section: Frequency Factor (Lnaa)mentioning
confidence: 98%
See 2 more Smart Citations
“…The water content in FR3 at the end of the aging test was even lower than at the start, which means that the water was consumed during the process. Similar changing of water content is shown in [21,22], which suggests an accelerated aging rate in mineral oil compared to FR3, because hydrolysis, for which water is the reactant, is the main cause cellulose degradation of both Kraft and T910 [23]. Aramid has excellent chemical stability and is resistant to hydrolysis and oxidation, whose by-products, gas and water, are lower than the cellulose [24].…”
Section: Water Contentmentioning
confidence: 72%